Developing an ecological-economic assessment framework for urban wastewater systems: the case of Athens and Vils wastewater systems - Xenarios, Stefanos (Informa UK Limited, 2009)
To achieve a good ecological status as proposed by the European Water Framework Directive (WFD; 2000/60/EEC) large investments from urban wastewater authorities are required. The Directive anticipates that cost-effective plans and their economic benefits will offset the high costs required for wastewater upgrading projects. However, urban waste water authorities claim that cost-effective measures are already in place and that little improvement can be made. Current valuation studies have focused either on ecological elements or economic aspects without offering persuading evidence on the cost versus benefits of upgrading projects. To this aim, the current study developed an ecological-economic valuation framework for the comparative assessment of the ecologically sustainable levels in receiving waters and the associated economic effects. The central Wastewater Treatment Plant in Athens (Greece) and the small treatment plant in Vils (Austria) are used as representative case studies.